Effects of yttrium on the oxidation behavior of 304 stainless steel with coating by laser remelting in high temperature water - Mengnan Liu; Dongxu Chen; Yanan Wang; Yanwen Zhou; Junwei Zhang; Xiang Wang (Materials Research Express, 2020)
Effects of Y _2 O _3 on the oxidation behavior of 304 SS with coating by laser remelting after exposed to 290 °C water containing 3 ppm O _2 for 72 h were investigated. It was found that the corrosion behavior of remelted layer on 304 SS with the addition of Y _2 O _3 was completely different from that of 304 SS and remelted layer on 304 SS without the addition of Y _2 O _3 . More Cr _2 O _3 hematite oxides were formed around strengthening phase near the Y _2 O _3 particles. With increasing exposure time, a little number of Fe _3 O _4 spinel oxides were continuing formed on the surface outside the Mn/Si enrichment area. The growth of Fe _3 O _4 spinel oxides were hindered because of the massive Cr _2 O _3 hematite oxides around the Y _2 O _3 particles. Some small Fe _3 O _4 spinel oxides were formed. Finally, the types of oxide film formed on the surface of the remelted layer with the addition of Y _2 O _3 were mainly Cr _2 O _3 hematite oxides and a few of fine FeCr _2 O _4 spinel oxides. The addition of Y _2 O _3 in laser remelting layer can obviously change the corrosion behavior of 304 SS exposed to high temperature water and the related mechanisms are also discussed.